Development of a methodology for assessing innovation activities for management purposes for oil and gas companies - Aitimova, Diana; Alibekova, Gulnaz; Serikbayev, Serik; Shadiyeva, Aigul; Yesmagulova, Nurgul; Kamali, Karlygash; Ibadildin, Nurkhat; Primbetova, Saule (Eastern-European Journal of Enterprise Technologies, 2024)
The study focuses on the innovation activity of oil and gas companies, solving the problem of evaluating this activity and presenting the results: – the author's methodology for assessing the innovation activity of oil and gas companies has been developed, the results of which allow to fix the development point in the range of [0–0.5) – “Inert”), [0.5–0.7) – “Developing” and more than 0.7 – “Active”. For each range, management strategies for the future are recommended; – the 5 oil and gas companies were evaluated according to three criteria. In the group of indicators “Investments” the best result is Total (0.95), in the group of indicators “Human resources” all companies showed a high result, on patent activity the European companies have a high result (0.81–0.83). Kazakhstan organizations, having more than sufficient human resources in the R&D sector, are not financed at a competitive level, which leads to a low level of patent activity of companies; – according to the result of the innovation activity assessment, the companies were distributed as follows: “Inert” – TCO (0.43) and KPO (0.32), “Developing” – Shell and ENI (0.68), “Active” – Total (0.81). The results suggest that the calculated method for determining indicators can be used to assess the innovation activity of oil and gas companies, considering the production factor. The results highlight the development of a methodology for assessing the innovation activity of oil and gas companies based on three main criteria, aimed at improving management. The methodology can be used by oil and gas companies and government agencies interested in industry development